The relationship of organizational culture to job satisfaction of civil servants in security sectors: A field study - Alwadai, Mansour Ahmed; Al Madhab, Maadi Muhammad (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aims to identify the reality of the organizational culture in the General Directorate of Public Security and its relationship to the job satisfaction of civil employees working in this directorate, in order to gain a deeper understanding of the role of the organizational culture prevailing in security organizations in influencing the level of job satisfaction of the civil employees working in them, and those who are not subject to the military service regulations Rather, they work according to the civil service system, with the aim of reaching recommendations that contribute to achieving job satisfaction for those employees so that they contribute to raising the efficiency and effectiveness of security organizations. The descriptive-survey approach was used as a methodology to conduct this study, and the questionnaire was used as a tool for the study, as the study was applied to a sample of civil employees in the General Directorate in Riyadh, whose number reached (120), and a number of results were reached, the most important of which are (low level of job satisfaction among employees Civilians working in public security, and the existence of a direct statistically significant relationship at the level (0.01) between organizational culture and job satisfaction of civil employees working in security sectors). The study recommended the necessity to reconsider granting civil servants working in the security sectors salaries, incentives and allowances commensurate with their duties, and that is comparable to what is granted to their fellow military personnel who carry out the same tasks, which contributes to increasing the level of their loyalty and affiliation with the security sectors in which they work. Developing the career path for civil employees working in the security sectors, in line with their job capabilities, educational levels and job grades, as well as working to increase the awareness of leaders in the security sectors of the importance of organizational culture in creating a positive organizational climate that encourages creativity and productivity and enhances levels of loyalty, belonging and organizational commitment and increases of the motivation of the employees.